Characterization of the complete plastome of Alopecurus aequalis (Poaceae), a widespread weed - Wang, Rong (Mitochondrial DNA B Resour, 2019)
Alopecurus aequalis is a predominant weed species that distributes widely in North temperate regions. The complete plastome of A. aequalis is reported here. It is a circular molecular of 136,382 bp in length and consists of a large single-copy region (LSC: 80,455 bp), a small single-copy region (SSC: 12,849 bp), and two inverted repeats regions (IRs: 21,539 bp). GC content is 38.3%. This plastome encodes 112 unique genes, including 78 protein-coding genes, 30 tRNAs, and 4 rRNAs. Phylogenetic tree shows that A. aequalis is sister to Poa annua.